Vasopressin pada Manajemen Syok Septik - Iswandi Darwis; Rizka Humardewayanti Asdie; Neema Putri Prameswari (CV. Jasa Sukses Abadi, 2021)
Sepsis is a systemic inflammatory response caused by an infection, which can involve multiple organs. Sepsis and multiple organ dysfunction syndrome (MODS) are the main causes of death in the intensive care unit of a hospital. In sepsis, septic shock, defined as sepsis-induced persistent hypotension despite adequate fluid resuscitation causing tissue hypoperfusion, can occur. Norepinephrine and dopamine are the vasopressors of choice for initial treatment septic shock, but the use of high-dose catecholamine vasopressors can cause adrenergic side effects that can increase mortality. Therefore, a septic shock patient with increased heart rate, it is necessary to use a vasopressor that does not cause adrenergic side effects. Vasopressin is a hormone secreted by the posterior pituitary. In hypotensive condition, vasopressin physiologically helps maintain blood pressure by acting as a potent vasoconstrictor. Vasopressin administration does not cause side effects caused by adrenergic stimulation such as increased tissue oxygen demand, decreased renal and mesenteric flow, increased pulmonary resistance and arrhythmias. This literature review also discusses the effects of vasopressin on blood pressure, the cardiovascular system, the immune system, the coagulation system, the respiratory system, the urinary system and the central nervous system in patients with septic shock.